Cloud resolving modeling of air sea interactions over the Western Pacific - Costa, Alexandre Araújo, author; Cotton, William R., advisor; Pielke, Roger A., committee member; Randall, David A., committee member; Rutledge, Steve A., committee member; Krueger, David A., committee member (Colorado State University. Libraries, 2000)
A cloud-resolving model (CRM) was used to simulate convection over the Western Pacific, during the Tropical Ocean Global Atmosphere Coupled Ocean - Atmosphere Response Experiment (TOGA-COARE). Simulations were performed either using prescribed sea surface temperatures (SSTs) or coupling the atmospheric model to an upper-ocean model (UOM). An uncoupled control simulation (CONTROL) was performed in which observed, time-evolving, SSTs were used as a lower boundary condition. The CRM was able to properly represent the evolution of the observed cloud systems. The similar statistics within an ensemble of multiple realizations of CONTROL (ENS1 to ENS4) confirmed its robustness. Sensitivity experiments using the uncoupled CRM were carried out, in which the sea surface temperature was increased (SST+) or decreased (SST-) by one degree Celsius and the same evolving large-scale forcing used in CONTROL. The convective-stratiform partition of the cloud systems was altered; the convective part being favored in SST+ and the stratiform part favored in SST-. In order to investigate the influence of inhomogeneous surface forcing, sinusoidal SST perturbations of different wavelengths were superimposed onto the observed SST in the uncoupled CRM. The inhomogeneous forcing changed the organization of the cloud systems in space and time. The CRM-UOM with high vertical resolution in the upper oceanic levels was used to investigate air-sea interactions in 10-day long simulations, representing two different regimes of COARE convection. Simulated atmospheric and oceanic fields were realistic. The model simulated the formation of precipitation-produced, stable freshwater lenses at the top of the ocean mixed layer, with a variety of horizontal dimensions and lifetimes. The simulated fresh anomalies showed realistic features, such as a positive correlation between salinity and temperature, the development of a surface jet in the direction of the wind and downwelling (upwelling) on its downwind (upwind) edge. The dataset generated by the coupled model was used to investigate the influence of SST changes in the apparent heat source and apparent moisture sink profiles. Finally, two 70-day coupled simulations were performed, with and without the salinity effect. No evidence was found that, at least in such timescale, the salt-stratification helps the maintenance of high SSTs over the Western Pacific.
Keywords: atmosphere; oceanography